Innovative prestressing technique using curved shape memory alloy reinforcement. (30th March 2020) - Zhao, Hang; Andrawes, Bassem
Highlights: New technique using SMA is proposed to apply external prestressing at local areas. Precast prestressing plate (PPP) is effective in applying local prestressing. Curved SMA is effective in developing self-anchorage mechanism. Connecting PPP to concrete using steel anchors and/or epoxy is effective. Abstract: Concrete prestressing techniques have been widely used in various structural applications. However, the application of local prestressing has been limited due to complexities related to the on-site implementation of anchorage devices and mechanical jacking systems. In this work, a novel method is introduced to apply local prestressing using curved Shape Memory Alloy (SMA) reinforcement. The experimental part of the study involves casting and prestressing a mortar plate with embedded curved prestrained SMA wire. The prestressing of the SMA wire is conducted by applying temperature using electrical resistivity. Next, an experimental study is carried out to explore the feasibility of using a mortar plate with embedded SMA as a precast prestressing plate (PPP) for existing concrete. A comparison is carried out between different installation methods to ensure effective connection between the PPP and concrete. Digital Image Correlation (DIC) and strain gage measurements are adopted to monitor the value and distribution of prestress in specimens. The experimental results are used to validate a Finite Element (FE) model of the SMA-reinforced PPP. The model is used to conduct a parametric study to explore the effect of SMA geometric configuration on the prestressing level. The experimental and numerical results show that the proposed prestressing technique is valid and can be used effectively for local prestressing.